A implementação do programa Expansão (2003) e do REUNI (2007) na UFTM - Zago, Jacqueline Oliveira Lima (2013)
This work is the result of the research process undertaken by the Post-Graduate Program in Education (PPGED) of the Federal University of Uberlandia (UFU) line of Research Labor, Society and Education (TSE). This work seeks to understand the transformation and expansion of the Federal University of Triangulo Mineiro (UFTM) occurred from 2005 which had its apex with the REUNI Program in 2007. For this, it was chosen to insert this institution in a broader context of education reform and specifically the Higher Education undertaken in Brazil from 90 years in the reconfiguration of the state\'s role in his project of society. The policy of expansion slots for education in higher education through University Reform, Program Expansion (2003) and REUNI (2007) was questioned throughout the text. This study aimed to identify the challenges presented to the academic community UFTM, from the documents listed for this research and how it was organized to materialize this project. Finally, the study presents specific data of expansion of UFTM formalized in Management Reports, Census and PingIFES identifying the main changes in the physical setting, people and configuration of the management in the implementation of this process.